The Power of Silence: Review of Kalpana Rahita Seshadri, HumAnimal: Race, Law, Language - Chrulew, Matthew (Humanimalia, 2014)
Kalpana Rahita Seshadri, HumAnimal: Race, Law, Language (Posthumanities 21). Minneapolis & London: University of Minnesota Press, 2012. 320 pp. 75.00 hb. 25.00 pb.